2013
DOI: 10.1038/jhh.2013.62
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypertension on vascular remodeling in patients with psoriatic arthritis

Abstract: We studied the impact of hypertension along with traditional and new cardiovascular risk factors on the structural and functional properties of arteries in psoriatic arthritis (PsA) patients. We examined 42 PsA subjects (aged 51±9 years) stratified according to hypertensive status (19 normotensive, PsA-NT and 23 hypertensives, PsA-HT). Thirty-eight normotensive subjects (C-NT) and 23 hypertensives (C-HT) comparable by age and sex served as controls. Mean carotid intima-media thickness (mean-IMT) and mean of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…The prevalence of increased subclinical atherosclerosis has been studied previously in PsA through the assessment of CIMT and FMD, but the partial exclusion of traditional cardiovascular risk factors, cardiovascular events, or concomitant medications have led to ambiguous results. 5,16,17 Hence, we excluded PsA patients with traditional cardiovascular risk factors, manifest CVD or on medications likely to influence vascular function (TNF-α inhibitors, steroids, β blockers, angiotensin-converting enzyme inhibitor, angiotensin receptor blocker, statins, aldosterone antagonist, and peroxisome proliferator-activated receptor).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of increased subclinical atherosclerosis has been studied previously in PsA through the assessment of CIMT and FMD, but the partial exclusion of traditional cardiovascular risk factors, cardiovascular events, or concomitant medications have led to ambiguous results. 5,16,17 Hence, we excluded PsA patients with traditional cardiovascular risk factors, manifest CVD or on medications likely to influence vascular function (TNF-α inhibitors, steroids, β blockers, angiotensin-converting enzyme inhibitor, angiotensin receptor blocker, statins, aldosterone antagonist, and peroxisome proliferator-activated receptor).…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that carotid IMT was significantly higher in the PsA group compared to healthy controls and remained significant when PsA patients were divided into subgroups with and without risk factors for cardiovascular disease (CVD) [10]. When the carotid IMT cut-off point of 95 percentile for age, gender and race was included with the presence of known CVD risk factors (obesity, smoking, hypertension), an increase in carotid IMT was associated with an increase in the 10-year risk of coronary artery disease by 14% [10, 1416]. It suggests that psoriatic arthritis is an independent risk factor for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Comme cela a été rapporté dans la littérature, le taux du TNF-␣ circulant augmenta après traitement anti-TNF-␣ [31,32]. En considérant que le TNF-␣ est un des plus importants médiateurs de l'inflammation et de la dysfonction endothéliale [33] et que et que l'EIM moyenne et la M-Max sont corrélées aux taux du TNF-␣ sérique de faç on significative [34], des niveaux éle-vés de TNF-␣ pourraient être responsables de la progression du dommage vasculaire dans le RP. En fait, l'évaluation du risque CV chez les patients ayant un RP semble être sous-estimée en utilisant les scores de risque habituels ; ainsi d'autres facteurs doivent expliquer la progression de l'athérosclérose malgré un traitement approprié [35].…”
Section: Discussionunclassified